2012
DOI: 10.1126/science.1212665
|View full text |Cite
|
Sign up to set email alerts
|

Untangling Genomes from Metagenomes: Revealing an Uncultured Class of Marine Euryarchaeota

Abstract: Ecosystems are shaped by complex communities of mostly unculturable microbes. Metagenomes provide a fragmented view of such communities, but the ecosystem functions of major groups of organisms remain mysterious. To better characterize members of these communities, we developed methods to reconstruct genomes directly from mate-paired short-read metagenomes. We closed a genome representing the as-yet uncultured marine group II Euryarchaeota, assembled de novo from 1.7% of a metagenome sequenced from surface sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
419
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(458 citation statements)
references
References 64 publications
25
419
3
Order By: Relevance
“…Little is known about the physiology or metabolism of the enigmatic MGII archaea (Euryarchaeota) despite their moderate abundance in both surface and deep marine waters (Pernthaler et al, 2002;DeLong et al, 2006;MartinCuadrado et al, 2008). The recent reconstruction of a MGII genome from surface seawater metagenomic data suggested a photo-heterotrophic lifestyle focused on degradation of protein and lipids (Iverson et al, 2012). The MGII OTUs that are enriched in GB plumes share only 86-87% 16S rRNA gene sequence identity with the population described by Iverson et al (2012), and we found no evidence for proteorhodopsin genes in our metagenomic or metatranscriptomic data sets, thus the GB MGII populations may be quite distinct from their surface water relatives.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…Little is known about the physiology or metabolism of the enigmatic MGII archaea (Euryarchaeota) despite their moderate abundance in both surface and deep marine waters (Pernthaler et al, 2002;DeLong et al, 2006;MartinCuadrado et al, 2008). The recent reconstruction of a MGII genome from surface seawater metagenomic data suggested a photo-heterotrophic lifestyle focused on degradation of protein and lipids (Iverson et al, 2012). The MGII OTUs that are enriched in GB plumes share only 86-87% 16S rRNA gene sequence identity with the population described by Iverson et al (2012), and we found no evidence for proteorhodopsin genes in our metagenomic or metatranscriptomic data sets, thus the GB MGII populations may be quite distinct from their surface water relatives.…”
Section: Discussioncontrasting
confidence: 37%
“…The recent reconstruction of a MGII genome from surface seawater metagenomic data suggested a photo-heterotrophic lifestyle focused on degradation of protein and lipids (Iverson et al, 2012). The MGII OTUs that are enriched in GB plumes share only 86-87% 16S rRNA gene sequence identity with the population described by Iverson et al (2012), and we found no evidence for proteorhodopsin genes in our metagenomic or metatranscriptomic data sets, thus the GB MGII populations may be quite distinct from their surface water relatives. However, if the heterotrophic characteristics of surface MGII groups do indeed extend to deep-sea MGII populations such as those in our data sets, the plume enhancement observed here may signal a heterotrophic response to enhanced primary production in the plume.…”
Section: Discussioncontrasting
confidence: 37%
“…Reference sequences from each OTU were also compared with a marine 16S rRNA sequence custom database according to Biers et al, 2009 using Smith-Waterman pairwise alignments (Smith and Waterman, 1981) and requiring sequence overlaps of X80%. HTCC2255 sequences were identified based on an alignment with the full-length 16S rRNA sequence available in the HTCC2255 metagenomic assembly of Iverson et al, 2012 because only a partial sequence was assembled in the genome of the original HTCC2255 culture. If possible, sequences were assigned to species level taxa with X97% identity across the overlap.…”
Section: Dmsp-carbon Calculationsmentioning
confidence: 99%
“…This is in large part due to our inability to culture most microorganisms in isolation, which is a prerequisite for traditional sequencing (Amann et al 1995). While shotgun sequencing and assembly of environmental samples is possible, assembly into complete genomes is generally only feasible for simple microbial communities (Tyson et al 2004;Venter et al 2004;Hess et al 2011;Iverson et al 2012). Moreover, these assemblies are actually consensus genomes derived from closely related species or strains, which makes many interesting analyses of genomes and populations impossible.…”
mentioning
confidence: 99%